2015
DOI: 10.1371/journal.pone.0138561
|View full text |Cite
|
Sign up to set email alerts
|

Effortless Attention as a Biomarker for Experienced Mindfulness Practitioners

Abstract: ObjectiveThe present study aimed at comparing frontal beta power between long-term (LTM) and first-time meditators (FTM), before, during and after a meditation session. We hypothesized that LTM would present lower beta power than FTM due to lower effort of attention and awareness.MethodsTwenty one participants were recruited, eleven of whom were long-term meditators. The subjects were asked to rest for 4 minutes before and after open monitoring (OM) meditation (40 minutes).ResultsThe two-way ANOVA revealed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Still, there are noticeably findings in other bandwidths: Dentico et al ( 2018 ) evaluated meditators before and after long CDM and ADM practices reporting an enhanced activity in frequency bands ranging from delta to low-gamma over midline prefrontal and left centro-parietal electrodes, with the higher spatial extent in the theta range. Tanaka et al ( 2015 ) reported that open monitor meditators (CDM-OM) had lower frontal power in beta during both meditation and baseline. For the delta band, Kim et al ( 2014 ) reported an increase solely in this bandwidth when comparing autogenic meditation (CDM-FA) with baseline, Baijal and Srinivasan ( 2010 ) also reported increases not only in these frequencies, but also in alpha for Sahaj Samadhi (CDM-FA).…”
Section: Spectral Featuresmentioning
confidence: 99%
“…Still, there are noticeably findings in other bandwidths: Dentico et al ( 2018 ) evaluated meditators before and after long CDM and ADM practices reporting an enhanced activity in frequency bands ranging from delta to low-gamma over midline prefrontal and left centro-parietal electrodes, with the higher spatial extent in the theta range. Tanaka et al ( 2015 ) reported that open monitor meditators (CDM-OM) had lower frontal power in beta during both meditation and baseline. For the delta band, Kim et al ( 2014 ) reported an increase solely in this bandwidth when comparing autogenic meditation (CDM-FA) with baseline, Baijal and Srinivasan ( 2010 ) also reported increases not only in these frequencies, but also in alpha for Sahaj Samadhi (CDM-FA).…”
Section: Spectral Featuresmentioning
confidence: 99%
“…Recent efforts from 38 research teams showed that breath counting during meditation sessions was associated with 39 higher mindfulness skills and could be considered in future investigations as a behavioral 40 measure of mindfulness skills [69]. Furthermore, measures of effortless attention could also 41 be included as a biomarker of mindfulness practice for experienced meditators [70].…”
mentioning
confidence: 99%
“…This highlights the need for more ‘length of practice’ demarcations in mindfulness studies and suggests that highly advanced practitioners may indeed function at levels that standardized self-report mindfulness measures cannot always identify (Tanaka et al, 2015). The use of self-report measures with a broader range, or ones that evaluate expected gains of meditators such as non-attachment (Sahdra et al, 2015), could be coupled with an EEG evaluation to better map neuroscientific differences.…”
Section: Discussionmentioning
confidence: 99%